PENINGKATAN PARTISIPASI MASYARAKAT DALAM PERENCANAAN DAN PEMBANGUNAN INFRASTRUKTUR DESA JAYALAKSANA - Hartomi, Hartomi; Sopandi, Andi; Irham, Irham (An-Nizam, 2023)
Community service activities related to increasing community participation in infrastructure planning and development aim to find out and analyse community participation in infrastructure development and see the supporting factors for community participation in the implementation of development in Jayalaksana Village, Cabang Bungin District. The methods used are community education and training. Meanwhile, the data collection techniques used in this research are direct observation and implementation of the programme at the location and documentation. The results of this service activity show that the participation of the Jayalaksana Village community in infrastructure development is quite good, because the community provides assistance in the form of thoughts, and labour. This shows that some community members know and are active in a series of community service activities carried out to minimise damage to village infrastructure due to littering by some people. There are several things that influence the community in participating, the existence of socialisation, opportunity, and leader factors.